(3MGTjI GdHGLhQj Ydi TQM GHf bGSe deJf CHj TLGYs - (3GdHGLhQj, EHQGgje Hf eMeO Hf CMeO, J(B1277(3g`s ((3YHO GddWja Hf GdSjO eMeO MehTs)
(3ChdgG (B:s
(3GdMeO ddg GdPj gOGfG dWQjbg Gdbhje(B...(3CeG HYO ajbhd GdYHO GdabjQ(B...(3GdHGLhQj(B...(3Efg bO cKQ GdfaY hGdGfJaGY HTQM GHf bGSe GdZRj Ydi CH TLGY(B...s
(3BNQgG (B:s
(3hdG jchf ebQG Ydi GdCUM Ef bGd hcdJc dJbQ dadGf HCda dg Ydnqj(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdGYdGe(B:(3L(B1(3,U(B71s
(3EjVGM Gdecfhf(B:(3L(B2(3,U(B448s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3Gdabg GdTGaYjs